To Engage or not to engage: influence of political talk shows in Bangladeshi youth through the lens of Information Adoption Model (IAM) - Jahangir, Karishma Binte (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.